A Macaque Model of Mesial Temporal Lobe Epilepsy Induced by Unilateral Intrahippocampal Injection of Kainic Acid - Chen, Ning (Public Library of Science, 2013)
OBJECTIVE: In order to better investigate the cause/effect relationships of human mesial temporal lobe epilepsy (mTLE), we hereby describe a new non-human primate model of mTLE. METHODS: Ten macaques were studied and divided into 2 groups: saline control group (n = 4) and kainic acid (KA) injection group (n = 6). All macaques were implanted bilaterally with subdural electrodes over temporal cortex and depth electrodes in CA3 hippocampal region. KA was stereotaxically injected into the right hippocampus of macaques. All animals were monitored by video and electrocorticography (ECoG) to assess status epilepticus (SE) and subsequent spontaneous recurrent seizures (SRS). Additionally, in order to evaluate brain injury produced by SE or SRS, we used both neuroimaging, including magnetic resonance image (MRI) & magnetic resonance spectroscopy (MRS), and histological pathology, including Nissl stainning and glial fibrillary acid protein (GFAP) immunostaining. RESULTS: The typical seizures were observed in the KA-injected animal model. Hippocampal sclerosis could be found by MRI & MRS. Hematoxylin and eosin (H&E) staining and GFAP immunostaining showed neuronal loss, proliferation of glial cells, formation of glial scars, and hippocampal atrophy. Electron microscopic analysis of hippocampal tissues revealed neuronal pyknosis, partial ribosome depolymerization, an abnormal reduction in rough endoplasmic reticulum size, expansion of Golgi vesicles and swollen star-shaped cells. Furthermore, we reported that KA was able to induce SE followed by SRS after a variable period of time. Similar to human mTLE, brain damage is confined to the hippocampus. Accordingly, hippocampal volume is in positive correlations with the neuronal cells count in the CA3, especially the ratio of neuron/glial cell. CONCLUSIONS: The results suggest that a model of mTLE can be developed in macaques by intra-hippocampal injection of KA. Brain damage is confined to the hippocampus which is similar to the human mTLE. The hippocampal volume correlates with the extension of the hippocampal damage.